PENGARUH GAYA HIDUP DAN LITERASI KEUANGAN DIGITAL TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN SHOPEE PAYLATER PADA GENERASI Z DI KOTA BANJARMASIN - Nur Lathifah; Novia Nour Halisa; Setio Utomo; Nurul Wahyuni (Smart Business Journal (SBJ), 2026)
The rapid digitalization of finance, manifested through the development of financial technology (fintech), has opened up access to more inclusive financial services for the public, including Buy Now Pay Later (BNPL)-based payment services such as Shopee PayLater. This service has been widely utilized by Generation Z in Banjarmasin City, where the decision to use the service is inseparable from various factors, such as their lifestyle patterns and their digital financial literacy. This study was conducted with the aim of identifying and testing these two factors as determinants influencing Generation Z in Banjarmasin City's decision to use Shopee PayLater services. This study applied a quantitative approach with an explanatory research design, a non-probability sampling technique in the form of an accidental sampling method. This study involved 100 Generation Z who had actively used Shopee PayLater services at least twice within the six months prior to the study. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software version 32. The findings demonstrate that lifestyle and digital financial literacy are significant factors influencing Generation Z in Banjarmasin City in their decision to use Shopee PayLater services, both partially and simultaneously.